WATER QUALITY AT RACH GIA MONITORING STATION (1997-2015) - Vinh, Le Thi; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2017)
Analysis results of coastal water samples in Rach Gia monitoring station from 1997 to 2015 showed that the values of the basic parameters (salinity: 0 - 32.2‰, pH: 7.01 to 8.52, concentration of total suspended solids: 3.5 - 770 mg/l; DO: 2.92 - 9.70 mg/l), BOD5: 0.90 - 9.76 mg/l, nutrients (ammonium: 0 - 316 μgN/l; nitrite: 0 - 330.1 μgN/l; nitrate: 62 - 2,470 μgN/l; phosphate: 2.2 - 93.1 μgP/l; silicate: 208 - 5,770 μgSi/l); organic matters (N: 608 - 1,670 μg/l; P: 48 - 748 μg/l), heavy metals (Zn: 6.8 - 43.4 μg/l; Cu: 0.6 - 14.7μg/l; Pb: 0.3 - 6.8 μg/l; As: 2.6 - 11.9 μg/l; Cd: 0.03 - 1.1 μg/l; Hg: 0.10 - 0.93 μg/l), hydrocarbons (116 - 788 μg/l) and coliform density (2-19,200 MPN/100 ml) changed widely. Seasonal variation indicated that in the dry season, salinity, pH, BOD5, concentration of nitrite, nitrate, org P and coliform density were higher; concentration of total suspended solids, phosphate, silicate, org N were lower compared to those in the rainy season. Tidal difference of surveyed parameters was comparatively observed only in dry season. The analysis of environmental data during nearly the last two decades showed that the variation trend of most parameters over time was not stable, concentration of DO was quite low and that of nutrient was quite high sometimes